2019
DOI: 10.3390/ijms20081832
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles and Carried miRNAs in the Progression of Renal Cell Carcinoma

Abstract: The formation and maintenance of renal cell carcinomas (RCC) involve many cell types, such as cancer stem and differentiated cells, endothelial cells, fibroblasts and immune cells. These all contribute to the creation of a favorable tumor microenvironment to promote tumor growth and metastasis. Extracellular vesicles (EVs) are considered to be efficient messengers that facilitate the exchange of information within the different tumor cell types. Indeed, tumor EVs display features of their originating cells and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 110 publications
0
45
0
Order By: Relevance
“…Exosomes transport a distinct molecular cargo of proteins and nucleic acids (mRNA, miRNA and genomic dNA) in peripheral blood (PB) and other bio-fluids (e.g., urine and saliva), and are recognized as relevant for the diagnosis and prognosis of certain pathologies, particularly solid tumors. Several studies have demonstrated that the proteins and nucleic acids contained within the exosomes of cancer patients can be isolated and identified as exosomal markers associated with cancer evolution (1)(2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Exosomes transport a distinct molecular cargo of proteins and nucleic acids (mRNA, miRNA and genomic dNA) in peripheral blood (PB) and other bio-fluids (e.g., urine and saliva), and are recognized as relevant for the diagnosis and prognosis of certain pathologies, particularly solid tumors. Several studies have demonstrated that the proteins and nucleic acids contained within the exosomes of cancer patients can be isolated and identified as exosomal markers associated with cancer evolution (1)(2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…The corresponding ligands CXCL12 and CCL21 are present at elevated levels in lymph nodes, lung, liver and bone marrowpreferred distant metastatic sites of breast cancer (288,290). (b) The formation of a pre-metastatic niche (PMN) (290)(291)(292)(293)(294)(295)(296). It is the result of the ability of respective solid tumors, already before tumor cell embolization occurs, to weaken defense mechanisms which are directed against tumor cells in potential host organs.…”
Section: Pathomechanisms Leading To Ispmmentioning
confidence: 99%
“…By disturbing humoral and cellular defense mechanisms in host organs, the subsequent tumor cell embolization and colonization can take place successfully and metastases can form in this organ. The formation of a PMN requires the interaction of three components: primary tumor derived components (273,296,297), tumor mobilized bone marrow derived cells (298) and organ components of the future host organ (292,294,299,300). In pre-metastatic niche formation, the capabilities of tumor cells and host organs are involved, this causes organotropy in niche formation (294).…”
Section: Pathomechanisms Leading To Ispmmentioning
confidence: 99%
“…Moreover, increased levels of miR-210 are directly correlated with poor patient outcomes, suggesting that it could be a potential biomarker for RCC diagnosis and prognosis [27]. The significance of miRNAs in RCC has been comprehensively summarized in a recent excellent review [28]. Accumulating evidence also suggests the involvement and potential importance of lncRNAs in gene regulation in human diseases, including RCC [29,30].…”
Section: Introductionmentioning
confidence: 99%